2013
DOI: 10.1007/s00213-012-2962-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intranasal oxytocin prior to encoding and retrieval on recognition memory

Abstract: Our findings indicate that OXT facilitates the processing of negative social stimuli during memory encoding and retrieval, possibly by enhancing the perception of aversive aspects in social situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Third, OT may improve other non-social cognition that in turn supports patients’ social cognitive abilities. As evidence, previous research indicates that OT administration to patients with SZ improves verbal memory (Feifel et al, 2012) and that OT administration to healthy individuals improves memory for negative social stimuli (Weigand et al, 2013). Consistent with this, our findings suggest that OT improved performance on social tasks requiring semantic processing and episodic memory (i.e., SI-E), but not on tasks that did not require such abilities (e.g., SSR and EET).…”
Section: Discussionmentioning
confidence: 86%
“…Third, OT may improve other non-social cognition that in turn supports patients’ social cognitive abilities. As evidence, previous research indicates that OT administration to patients with SZ improves verbal memory (Feifel et al, 2012) and that OT administration to healthy individuals improves memory for negative social stimuli (Weigand et al, 2013). Consistent with this, our findings suggest that OT improved performance on social tasks requiring semantic processing and episodic memory (i.e., SI-E), but not on tasks that did not require such abilities (e.g., SSR and EET).…”
Section: Discussionmentioning
confidence: 86%
“…Mentalizing tasks require participants to recall previously stored memories of other persons´ mental states and their corresponding facial expressions and match them to the stimuli presented. A number of studies have demonstrated the potential of OXT as an enhancer for memory processes (Savaskan et al, 2008;Guastella et al, 2008b;Weigand et al, 2013). These studies gain empirical support from neuroanatomical findings, for example OXT receptors have been found in brain circuitries underlying memory processes namely the hippocampus and the septum (Gimpl and Fahrenholz, 2001;Meyer-Lindenberg et al, 2011).…”
Section: Page 14 Of 29mentioning
confidence: 92%
“…The use of intranasal OXT in experiments in humans has led to the promising hypothesis that OXT is capable of modulating a wide range of complex social-cognitive functions. Specifically, previous studies have shown that OXT facilitates social memory (Savaskan et al, 2008;Guastella et al, 2008b;Weigand et al, 2013), reduces fear and anxiety (Heinrichs et al, 2003;Kirsch et al, 2005), and promotes social approach and trust (Kosfeld et al, 2005;Feldmann et al, 2007;Baumgartner et al, 2008). OXT administration has also been shown to enhance empathy (Hurlemann et al, 2010).…”
Section: Introductionmentioning
confidence: 93%
“…At the very least, alexithymia may serve to explain the poor reliability of oxytocin effects. While several studies have found positive effects of oxytocin, several other studies have failed to replicate these effects (Lischke et al, 2012;Scheele et al, 2012;Weigand et al, 2013), even when experimental tasks have been shown to rely upon interoception and to activate the anterior insula . As demonstrated by Luminet and colleagues (2011), the effects of oxytocin may be limited to those high in alexithymia, suggesting that measuring A c c e p t e d M a n u s c r i p t 11 alexithymia may represent an easy, a priori, method for identifying those who may be helped by oxytocin administration.…”
Section: Summary and Outstanding Questionsmentioning
confidence: 92%